Treatment of corticosteroid-induced tibial osteonecrosis – decompression and tibial intramedullary nail: a case report - Szejnfeld Mann, Tânia (Journal of the Foot & Ankle, 2026)
Clandestine injections of industrial liquid silicone for aesthetic purposes, especially in transgender women, can cause late complications, including distal migration of the silicone, foreign body granuloma, and opportunistic infection, even years after the procedure. Diabetic patients with a history of repeated infiltrations are particularly susceptible. A 56-year-old transgender woman, diabetic, presented with chronic plantar pain initially treated as plantar fasciitis, with eight corticosteroid infiltrations, without improvement. It evolved with edema and hyperemia in the hallux, suggestive of gouty arthritis. Preoperative magnetic resonance imaging suggested calcaneal osteomyelitis and plantar collections. During surgery, in the calcaneal region, clear liquid similar to that previously drained from the forefoot was found. A bone fragment collected from the calcaneus was positive for Candida parapsilosis, sensitive to caspofungin, amphotericin B, and voriconazole, and resistant to fluconazole. Distal plantar collection showed migrated silicone and a foreign body reaction. The case shows late migration of industrial silicone from the gluteal region to the foot, with a granulomatous reaction and opportunistic osteomyelitis due to Candida parapsilosis, probably facilitated by repeated corticosteroid infiltrations in diabetic patients. This scenario is rarely described in the literature, especially in cases involving bone. In transgender women with a history of industrial silicone and chronic plantar pain, subcutaneous collections and signs of osteomyelitis may represent opportunistic fungal co-infection. Accurate diagnosis, collection of material for specific cultures, and multidisciplinary management (orthopedics, infectious diseases, surgery/plastic surgery) are essential for functional preservation and clinical cure.